Revealing the influence of systemic risks in the development of enterprises on updating their investment position under entropy conditions - Mushnykova, Svitlana; Prokhorova, Viktoriia; Babichev, Anatoliy; Abernikhina, Iryna; Karlova, Olena; Babiak, Nataliia (Eastern-European Journal of Enterprise Technologies, 2024)
This study identifies the impact of systemic risks on the company’s strategic development prospects through attracting investments and ensuring their insurance protection. The company’s strategic development model predetermines the level of its investment activity at various stages of the life cycle. This is important because there is an urgent need for the Ukrainian economy to attract foreign investment for the post-war reconstruction of the country. But there are objective difficulties associated with the complication of actualizing the investment position of enterprises in the leading sectors of the economy, taking into account the challenges and threats caused by the military aggression of the Russian Federation. Conditions of entropy, which indicate unpredictability and variability in the business environment, expose enterprises to great risks. It was determined that the investment position of the business entity should correlate with the strategic model of its development and represent a balanced mechanism. This has made it possible to reasonably systematize the risk of investment activities and approaches to their management. Statistical analysis became the basis for evaluating the dynamics of direct and capital investments in the leading sectors of the Ukrainian economy. The results gave grounds for asserting a significant deterioration of the investment climate in Ukraine as a result of the war. The level of direct and capital investments is low. We focused attention on the possibility of flexible adjustment of strategic development plans to unforeseen risks. The proposed recommendations, unlike existing ones, consist of a combination of state and market levers to stimulate investments in the economy of Ukraine. Existing military risks restrain the investment activity of stakeholders. Therefore, the conditions for the practical implementation of the mechanism of distribution and reduction of risks are the formation of insurance protection of investments for investors